The Role of Gut Microbiota in the Pathophysiology of Depression: A Narrative Review - Wojciechowska, Karolina; Zajkowska, Izabela; Zabrocka, Patrycja; Martowska, Julia; Choroszewska, Ewelina; Baran, Julia; Warych, Wiktor (Quality in Sport, 2026)
Depression is a complex psychiatric disorder with incompletely understood pathophysiology. Increasing evidence implicates gut microbiota dysbiosis in depression through the microbiota-gut-brain axis. This narrative review summarizes experimental and clinical studies published between 2013 and 2025 examining associations between gut microbiota and depressive disorders. Findings indicate that depression is linked to altered microbial diversity, immune activation, intestinal barrier dysfunction, dysregulation of the hypothalamic-pituitary-adrenal axis, and disturbances in tryptophan metabolism. While preclinical studies suggest a potential causal role of gut microbiota in depressive-like behavior, human evidence remains largely associative. Modulation of gut microbiota represents a promising but still exploratory direction for future depression research and therapy.